A study of the economic impacts of the TPP on Korea: Armington and Melitz model. (7th March 2016) - Roh, Jae-Whak; Oh, Kyungsoo
Abstract : Purpose: – The purpose of this paper is to measure the effects of TPP on Korean economy focussing on the changes in the number of firms and productivity. Design/methodology/approach: – Following Melitz (2003) and Balistreri et al. (2011), the authors apply CGE simulation to five groups of 140 countries. Findings: – The authors find that welfare increases in Korea to join the TPP regardless the size of the TPP through productivity improvement of participating firms and increases in the number of exporting firms, factor prices and outputs. Practical implications: – This study helps tentative member countries of TPP decide to join. Originality/value: – The effects of TPP to Korean economy is measured with Melitz model, which has not yet attempted before.